Statistical Parameters Estimation of Correlated Millimeter-Wave MIMO Channel - Maziar Kakavand; Mohammadreza Hassannejad Bibalan; Mina Baghani (Majlesi Journal of Electrical Engineering)
This paper proposes a novel approach based on the copula models for estimating Millimeter-Wave channel parameters with Rician fading in a correlated MIMO system. Even though the use of these waves faces numerous challenges, having an accurate estimation of their parameters would be a crucial notion for the improved performance of this channel. Since the considered system in this paper is a MIMO system with nearby transmitter antennas, the components of the received signals are correlated. However, a general model is not available for this kind of correlation. By taking into account the correlation, this model enables a precise Joint Probability Density Function (JPDF) by employing copula models for the received signals in the antennas. We also obtain more precise channel parameter estimates using this density function. The multi-path fading parameters in a MIMO system and the correlation coefficients between the transmitter and receiver antennas are both presented in this paper. Some simulations are employed to assess the validity and reliability of estimating Millimeter-Wave channel parameters in a MIMO system.